Penyisihan Kadar TDS, pH, Dan Total Coliform Dalam Pengolahan Air Hujan Menjadi Air Siap Minum: Allowance for TDS, pH, and Total Coliform Levels In The Treatment of Rainwater Into Ready-Drinking Water - Sri Anzjarwati; Loureni Santa Basilia; Reya Adiarti Aradiyah; Rizki Purnaini (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Rainwater is water that falls directly from the sky due to the evaporation process. Rainwater is commonly used as drinking water by the community. However, rainwater should not be consumed directly without prior processing. This is because rainwater is acidic and has low mineral content, and still contains bacteria that can cause disease. This study aims to design and determine the efficiency value of rainwater treatment equipment into ready-to-drink water with a combination of processing through filtration and electrolysis. The parameters that will be tested in this study are TDS, pH, and total coliform. After processing, it is known that the efficiency of the series of tools in this study in removing the total coliform content is 100% and the TDS is 73.81%. However, the pH value after processing has not met the quality standards